Treatment of Realia in the Subtitling of Ekphrastic Texts - Čemerin, Vedrana (Journal of Audiovisual Translation, 2019)
As far as the basic tenets and technical constraints of subtitling go, the subtitling of documentaries devoted to various types of visual arts does not differ significantly from subtitling performed with other types of audiovisual content. However, each source material has aspects that go beyond the technical framework, encompassing cultural idiosyncrasies and culture-specific references. A special place among such items belongs to realia, in the sense of words and phrases denoting concepts characteristic of one nation and foreign to another. This article narrows down the scope of its research of such phenomena to a corpus consisting of several art documentaries ranging in subject from Byzantine to Ottoman and Chinese art and translated from English into Croatian, examining the strategies used to deal with realia in ekphrastic texts and the overall treatment of the concepts which they denote, while at the same time providing insight into the role played by the visual experience given by subtitles as an integral part of the representational process. The paper is partially based on a talk given in February 2016 at the Audiovisual Representation conference in Rome but as the research project had been a work-in-progress, it has since been substantially revised and expanded.